Incentive edge caching in software‐defined internet of vehicles: A Stackelberg game approach. (12th August 2018) - Alioua, Ahmed; Senouci, Sidi‐Mohammed; Sedjelmaci, Hichem; Moussaoui, Samira
Summary: In this paper, we investigate an incentive edge caching mechanism for an internet of vehicles (IoV) system based on the paradigm of software‐defined networking (SDN). We start by proposing a distributed SDN‐based IoV architecture. Then, based on this architecture, we focus on the economic side of caching by considering competitive cache‐enablers market composed of one content provider (CP) and multiple mobile network operators (MNOs). Each MNO manages a set of cache‐enabled small base stations (SBS). The CP incites the MNOs to store its popular contents in cache‐enabled SBSs with highest access probability to enhance the satisfaction of its users. By leasing their cache‐enabled SBSs, the MNOs aim to make more monetary profit. We formulate the interaction between the CP and the MNOs, using a Stackelberg game, where the CP acts first as the leader by announcing the popular content quantity that it which to cache and fixing the caching popularity threshold, a minimum access probability under it a content cannot be cached. Then, MNOs act subsequently as followers responding by the content quantity they accept to cache and the corresponding caching price. A noncooperative subgame is formulated to model the competition between the followers on the CP's limited content quantity. We analyze the leader and the follower's optimization problems, and we prove the Stackelberg equilibrium (SE). Simulation results show that our game‐based incentive caching model achieves optimal utilities and outperforms other incentive caching mechanisms with monopoly cache‐enablers whilst enhancing 30% of the user's satisfaction and reducing the caching cost. Abstract : This paper investigates an incentive caching mechanism for an internet of vehicles (IoV) system based on the paradigm of software‐defined networking (SDN). A competitive cache‐enablers market composed of one content provider (CP) and multiple mobile network operators (MNOs) is studied. The interaction between the CP and the MNOs is formulated using a Stackelberg game. The proposed game‐based model achieves optimal utilities and outperforms other existing mechanisms with monopoly cache‐enablers while enhancing 30% the user's satisfaction and reducing the caching cost.